A Correlation Between Self-Efficacy and the use Of Long-Acting Contraceptive Methods Among Couples Of Reproductive Age in the Working Area of Lubuk Pinang Community Health Center in 2025 - Ria Devita Nurkhasanah; Nimas Ayu Lestari Nurjanah; Kintan Anissa (Multidisciplinary Journals, 2026)
The use of Long-Acting Contraceptive Methods (LACMs) is an important strategy in family planning programs due to their high effectiveness and low failure rates. However, the utilization of LACMs in the community remains relatively low, partly influenced by psychological factors such as self-efficacy. This study aims to determine the correlation between self-efficacy and the use of Long-Acting Contraceptive Methods among Couples of Reproductive Age in the working area of the Lubuk Pinang Health Center in 2025. This study employed a quantitative design with a cross-sectional approach. The population consisted of all Couples of Reproductive Age in the working area of the Lubuk Pinang Health Center, with a sample of 96 respondents selected using purposive sampling techniques. Data were collected using a self-efficacy questionnaire and contraceptive use data, then analyzed using univariate and bivariate methods with the Chi-Square test. The results showed that the majority of respondents had low self-efficacy, totaling 55 individuals (57.3%), and most used non-LACM methods, totaling 63 individuals (65.6%). Bivariate analysis indicated a significant correlation between self-efficacy and the use of LACMs (p-value = 0.000). Respondents with high self-efficacy were more likely to use LACMs compared to those with low self-efficacy. In conclusion, there is a significant relationship between self-efficacy and the use of Long-Acting Contraceptive Methods among Couples of Reproductive Age in the working area of the Lubuk Pinang Health Center in 2025. It is expected that healthcare providers can enhance the self-efficacy of Couples of Reproductive Age through education and counseling to increase the use of LACMs.